THE USE OF CULTURAL HERITAGE TO STUDY THE RUSSIAN LANGUAGE IN RUSSIA AND IN THE COUNTRIES OF THE ASIAN REGION - Sergey V. Zemlyukov; Sergey A. Manskov; Larisa I. Nekhvyadovich (Высшее образование в России)
The article presents the experience of the Altai State University in the use of cultural heritage to increase the level of proficiency in Russian by the Russians and migrants in Russia, as well as the practice of using Russia's cultural heritage to study the Russian language in Central Asian countries. Attention is drawn to the fact that the quality of University language education is becoming one of the factors influencing the promotion of Russian as a foreign language. One of the most effective solutions to be included in a number of areas of training in SCO University is linguistics as the Foundation for integrated language teaching.